Kajian Ketersediaan Air Tanah Terkait Pemanfaatan Lahan di Kabupaten Blitar - Widodo, Trisno (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
East Java Provincial Government has categorized Blitar Regency as water scarce area and is prone to drought therefore resulting in increasing use of groundwater. The study analyzed land use change during 2002-2011 period, water demand, infiltration, and groundwater supply. The study conducted land use analysis (through Landsat image interpretation), runoff and infiltration analysis (using hydro meteorological method), water demand analysis (for domestic, urban, farming, fishery and industry sectors), and groundwater reserve analysis (gap between infiltration and total demand). Interpretation of Landsat image from 2002 and 2011 indicated a significant increase in housing area while showing decrease in other uses which may serve as watershed area such as farmlands, forests, plantations and open spaces. Infiltration analysis indicated that in dry seasons (with very low or zero precipitation) infiltration is limited therefore creating a deficit in groundwater supply.Â  One of the driving factors is the conversion of open spaces into built areas in the last 10 years. The study recommended that the government should maintain the amount of open spaces and increase rain water infiltration by means of ponds, biopores, and absorption wells.